YOSH BOKSCHILARDA KUCHNI RIVOJLANTIRISH BO’YCHA TRENERLAR FIKRINI O’RGANISH - Usmanov Zokhidjon; Makhmudova Sadokathan (Journals Park Publishing, 2022)
Without a doubt, today boxing has become one of the favorite sports of the population of our country, especially young people. Our boxers have triumphed in almost all of the prestigious competitions held in the world rings since 2016 and are missing leadership.
Keywords: President, encouragement, boxing, athletes.